The elastic secrets of the chameleon tongue - Moulton, D; Lessinnes, T; O'Keeffe, S; Dorfmann, L; Goriely, A (Royal Society, 2016)
The ballistic projection of the chameleon tongue is an extreme example of quick energy release in the animal kingdom. It relies on a complicated physiological structure and an elaborate balance between tissue elasticity, collagen fibre anisotropy, active muscular contraction, stress release and geometry. A general biophysical model for the dynamics of the chameleon tongue based on large deformation elasticity is proposed. The model involves three distinct coupled subsystems: the energetics of the intralingual sheaths, the mechanics of the activating accelerator muscle and the dynamics of tongue extension. Together, these three systems elucidate the key physical principles of prey-catching among chameleonides.